Peran Inovasi, Kualitas Produk, dan Strategi Perusahaan dalam Mendorong Keberhasilan Bisnis: Studi Literatur - Imammudin, Yusuf; Arqy Ahmadi, Mirzam (Teewan Journal Solutions, 2025)
Business success is the primary goal for companies, especially in facing the increasingly intense competition in the global market. The dynamic changes in the market, technological advancements, and shifts in consumer preferences compel companies to continually innovate and adapt. This study aims to understand the role of innovation, product quality, and corporate strategy in supporting business success. Using a literature review approach, this research highlights how innovation is crucial not only in developing new products but also in improving the operational efficiency of companies. High product quality can enhance customer satisfaction and loyalty, leading to business growth. Additionally, an effective and flexible corporate strategy enables companies to better respond to market changes. The findings of this study demonstrate that the integration of innovation, product quality, and corporate strategy is key to achieving long-term business success. These insights provide practical and theoretical value for companies, academics, and policymakers in formulating more adaptive and sustainable business strategies.